LINGUISTIC FEATURES OF THE CONCEPT OF UGLINESS IN THE GREAT GATSBY BY F.SCOTT FITZGERALD (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
F. Scott Fitzgerald’s The Great Gatsby is often seen as a glamorous story about wealth and parties, but beneath that shiny surface lies a world of ugliness. This article explores how Fitzgerald shows us this ugliness, not just in how things look, but in how people act and what they value. We’ll see how the author uses descriptions of places, characters, and their choices to show the dark side of the Roaring Twenties, revealing a society obsessed with money and appearances while ignoring real human connection and moral values. This isn’t just about a story of failed love; it’s a look at how chasing the wrong dreams can lead to emptiness and destruction, and the ugly truths that can be hidden behind a pretty face